The Shifting View on the Prohibition of Exogamous Marriage among the Suku Anak Dalam Community - Hidayati, Rahmi; Ramlah, Ramlah (al-'adalah, 2020)
There have been many previous studies discussing on the theme of prohibition of endogamy and exogamous marriages, but this study will be more focused on the examining exogamous marriages in traditional societies among the Suku Anak Dalam community in Jambi Province. This study uses a combination of descriptive-empirical methods and literature studies. They are used to describe the results of several interviews with the informants and also supported by the literature studies related to the research objective. This study presents the results of empirical research on the determinant factors that influences the shifting of the perspective change on exogamous marriage among the Suku Anak Dalam community, which is analyzed through sociological and anthropological approaches. The result of this study shows that there have been social changes among the Suku Anak Dalam community in the field of family law, especially in matters of marriage law. The change of time, education, economy, religion, and the development of modern society have implicaton to the change of the paradigm of thinking among some of the Suku Anak Dalam community regarding on the prohibition of exogamous marriages.